The impact of L2 self-efficacy beliefs on a Chinese international student’s learning approaches - Yu, Hua; Wyatt, Mark (Journal of Academic Language and Learning, 2022)
Research that has explored changes in Chinese international students’ approaches to learning in Anglophone countries has tended to highlight the role of either conceptions of learning or new learning environments in shaping these changes. In contrast, little research has been done on how such changes occur within individual students. In this qualitative case study, we address this imbalance. Using data from classroom observations and semi-structured interviews, we explore in-depth how a Chinese law student, negotiating academic and linguistic challenges, moved from a surface to a deep learning approach. This student’s self-efficacy beliefs and mindset played a pivotal role in shaping his learning approaches in a second language environment. Pedagogical implications concerning the set-up of EAP programmes to support international students are highlighted.